2019
DOI: 10.1097/md.0000000000015597
|View full text |Cite
|
Sign up to set email alerts
|

Plasma C-terminal agrin fragment and rapid kidney function decline in chronic kidney disease patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Supporting this concept, several studies reported strong positive correlation between CAF concentration and creatinine (a well‐established marker of kidney functionality) and negative correlation between CAF and estimated GFR in patients with chronic kidney disease 96 and undergoing kidney transplantation 53,94 . In a 57‐week study, CAF was reported to have a high predictive power in determining rapid kidney function decline in patients affected by chronic kidney disease, independently from estimated GFR 97 . Hence, although the authors acknowledged that NMJ‐derived CAF may play a partial role also in the elevated concentrations observed among kidney‐dysfunctional patients, the presence of kidney‐related diseases seems an independent predictor of elevated CAF.…”
Section: Methodological Considerationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Supporting this concept, several studies reported strong positive correlation between CAF concentration and creatinine (a well‐established marker of kidney functionality) and negative correlation between CAF and estimated GFR in patients with chronic kidney disease 96 and undergoing kidney transplantation 53,94 . In a 57‐week study, CAF was reported to have a high predictive power in determining rapid kidney function decline in patients affected by chronic kidney disease, independently from estimated GFR 97 . Hence, although the authors acknowledged that NMJ‐derived CAF may play a partial role also in the elevated concentrations observed among kidney‐dysfunctional patients, the presence of kidney‐related diseases seems an independent predictor of elevated CAF.…”
Section: Methodological Considerationsmentioning
confidence: 91%
“… 53 , 94 In a 57‐week study, CAF was reported to have a high predictive power in determining rapid kidney function decline in patients affected by chronic kidney disease, independently from estimated GFR. 97 Hence, although the authors acknowledged that NMJ‐derived CAF may play a partial role also in the elevated concentrations observed among kidney‐dysfunctional patients, the presence of kidney‐related diseases seems an independent predictor of elevated CAF. In this context, particular attention should be paid when investigating CAF in diabetic patients, as this pathology is the leading cause of chronic kidney disease.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…53,94 In a 57-week study, CAF was reported to have a high predictive power in determining rapid kidney function decline in patients affected by chronic kidney disease, independently from estimated GFR. 97 Hence, although the authors acknowledged that NMJ-derived CAF may play a partial role also in the elevated concentrations observed among kidney-dysfunctional patients, the presence of kidneyrelated diseases seems an independent predictor of elevated CAF. In this context, particular attention should be paid when investigating CAF in diabetic patients, as this pathology is the leading cause of chronic kidney disease.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Interestingly, also renal function has been linked to raised levels of circulating CAF since this biomarker has been reported to be higher in patients developing acute kidney injury and undergoing kidney transplantation [55]. Reports showed CAF to have a high predictive power in determining rapid kidney function decline in patients affected by CKD, and – above that – CAF was cross-sectionally correlated to appendicular lean mass, handgrip, and gait speed from estimated glomerular filtration rate (GFR) [56].…”
Section: “The Good”: Assess and Monitor Muscle Mass Nutrition And Phy...mentioning
confidence: 99%
“…C-terminal agrin fragment (CAF) has been investigated as a neuromuscular junctiona related biomarker of muscle dysfunction [55][56][57][58]. Interestingly, also renal function has been linked to raised levels of circulating CAF since this biomarker has been reported to be higher in patients developing acute kidney injury and undergoing kidney transplantation [55].…”
Section: Biomarkersmentioning
confidence: 99%